"Covid-19 and Income Inequality in OECD Countries:" A Methodological Comment - Oded Stark (Institute of Labor Economics (IZA), 2023)
Wildman (2021), who identifies "a clear association between income inequality [measured by the Gini coefficient] and COVID-19 cases and deaths," concludes that "a goal of government should be to reduce [income] inequalities and [thereby] improve [the COVID-19 outcomes /] underlying health of their populations." In this Comment, we argue that reducing the Gini coefficient of the income distribution of a population need not weaken the population's social stress. It is this stress which is a source of adverse health outcomes of the population. Because a measure of this stress is a component of the Gini coefficient, reducing the coefficient can leave the measure as is, or even increase the measure.
Keywords: D01; D63; D91; I10; I14; I31; Z18; 330; social stress; Gini coefficient; income inequality; forming public health policy